Society perception towards security officers in Malaysia: the analysis - Maurice Budit, Vernon Valentine (2019)
Purpose–The purpose of the present study is to analyse the society perception towards security officers in Malaysia. Society perception towards security officers are based on five dimensions; First Impression on Security Officer, Security Officer Job, Professionalism and Integrity, Satisfaction with Security Officers and Image of Security Officers.